Las técnicas grafoplásticas para el desarrollo de la motricidad fina en los niños de preparatoria, de la escuela de educación básica doctor Daniel Rodas Bustamante de la ciudad de Loja. Periodo lectivo 2017 – 2018 - Yunga Ganazhapa, Yomayra Yessenia (2018)
The thesis entitled: THE GRAFOPLASTIC TECHNIQUES FOR THE DEVELOPMENT OF FINE MOTORCYCLES IN HIGH SCHOOL CHILDREN, OF THE DOCTOR DANIEL RODAS BUSTAMANTE EDUCATION SCHOOL OF THE CITY OF LOJA. LECTIVE PERIOD 2017 - 2018. Has as general objective: identify the influence of graphoplastic techniques in the development of fine motor of high school kids. Scientific, analytical - synthetic and descriptive methods were used. The instruments: an interview (teacher) and an observation guide (children). It shows 10 children (5 to 6 years) and 1 teacher. The results in the interview were: that the teacher sometimes applies graphoplastic activities during her work week, since she considers that they don´t stimulate any of the children's learning areas, much less that they favor the development of fine motor. The initial results of the observation guide reflect that: 100% of the children observed cann’t hold the pencil, paint or crayon with the index and thumb fingers; 70% of children do not model plasticine using the digital clamp and do not perform the arabesque technique without raising their hand, and 60% do not manage to perform slipped strokes, large and small progression exercises in narrow spaces; In addition, when taking as a reference the scale of evaluation of the psychomotor skills in the preschool of La Cruz and Mazaira (3 to 6 years) children have a low in their fine motor. With the application of the proposal the following progress is observed: 100% of children threading using their thumb and forefinger, perform the surface filling without leaving the contour of the figure, tear paper using your thumb and forefinger, puncture the line drawn and perform the slipped lines, large and small progression exercises starting from left to right; 80% folded paper following the idications given, and; 70% have control of their fine movements and perform the inscrpstion exercises correctly; where when taking as reference the scale of evaluation of the psychomotricity in preschool of the Cross and Mazaira (3 to 6 years) the children have a normal level in their fine motor. It is concluded that graphoplasts contribute to the development of fine motor. It is recommended to apply them from early ages and in the work days of children.